Optimalisasi Kualitas Jurnalisme Komunikasi Digital Portal Info Publik Solok - Bulan Sucitra; Wahyu Budi Priatna (Bahasa Indonesia, 2025)
Digital journalism quality in local government media still faces challenges in terms of accuracy, information balance, and transparency. This study focuses on analyzing journalism quality optimization strategies at the Info Publik Solok Portal to enhance the effectiveness of digital public communication. This is crucial due to increasing public demand for credible official information and the need for adaptive government media. A qualitative case study approach was used, with data collected through interviews, observations, and questionnaires. The results reveal strategies including human resource training, routine content evaluation, editorial role structuring, and the use of digital tools such as social media and Google Analytics. Transparency is reinforced by identifying journalists and applying open correction mechanisms. These efforts effectively support professional digital journalism practices and strengthen public trust in government media.